1972
DOI: 10.1677/joe.0.0550229
|View full text |Cite
|
Sign up to set email alerts
|

The Conversion of Angiotensin I to Angiotensin Ii by Rabbit Glomeruli

Abstract: Experiments were designed to test the possibility that glomeruli can convert angiotensin I (AI) to angiotensin II (AII) (Thurau, Dahlheim & Granger, 1969). In six experiments, 10\g=m\g(1-asp-5-ile) AI in 1\m=.\1 ml 0\m=.\15m-phosphate\p=m-\salinebuffer, pH 5\m=.\7, were incubated in stoppered neoprene tubes with 20-25 glomeruli dissected as previously described (Brown, Davies, Lever, Parker & Robertson, 1965) from kidneys of New Zealand White rabbits. The glomeruli were stored frozen, then thawed and incubated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
1

Year Published

1973
1973
1988
1988

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 4 publications
1
3
0
1
Order By: Relevance
“…This finding is in agreement with observations in the dog (di Salvo, Peterson, Montefusco & Menta, 1971 ;Aiken & Vane, 1972). For isolated glomeruli of rabbit kidney a mean conversion rate of 6.8% was found (Leckie, Gavras, McGregor & McElwee, 1972). However, it is possible that in the isolated rat kidney perfused with a cell-free medium, RPF is much higher than in vivo, and that the rapid passage of A1 through the kidney might limit its rate of conversion.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in agreement with observations in the dog (di Salvo, Peterson, Montefusco & Menta, 1971 ;Aiken & Vane, 1972). For isolated glomeruli of rabbit kidney a mean conversion rate of 6.8% was found (Leckie, Gavras, McGregor & McElwee, 1972). However, it is possible that in the isolated rat kidney perfused with a cell-free medium, RPF is much higher than in vivo, and that the rapid passage of A1 through the kidney might limit its rate of conversion.…”
Section: Discussionsupporting
confidence: 91%
“…Although circulating All has mainly been considered responsible for the effects in the kidneys, it also has been suggested that the intrarenal regulatory functions are performed by a second, tissuebound intrarenal renin-angiotensin system localized in the region of the juxtaglomerular apparatus (5). This hypothesis was supported by the fact that the enzymes involved in the metabolism of All are all located in this area (9)(10)(11). However, the microtopographical details ofthe localization ofthe various components of the renin-angiotensin system, particularly the exact site of generation of All, remained unclear.…”
mentioning
confidence: 97%
“…Renal converting enzyme may be located in the cell membrane, as it is in the lung, and Oshima et al (1974) suggest that it may be physically separated from the renal circulation to serve a local intrarenal function. Further, since isolated glomeruli have been shown to convert angiotensin I into angiotensin II (Leckie et al, 1972) and converting-enzyme activity has been measured in the juxtaglomerular apparatus (Granger et al, 1972) it is likely that the juxtaglomerular cells may contain converting enzyme in the cell membrane. Conversion of angiotensin I to angiotensin II may occur here or in more distal vessel walls, e.g.…”
Section: Discussionmentioning
confidence: 99%